A multiple-criteria approach for the evaluation of comparative indicators of sustainable tourism - Janošik, Marija; Popović, Gabrijela; Vukotić, Svetlana (Hotel and Tourism Management, 2023)
In this paper, a multiple-criteria approach has been applied to evaluate and rank types of development indicators of sustainable tourism. Groups of indicators whose comparison was presented through evaluation and prioritization are economy, the satisfaction of tourists, social and cultural elements, as well as environmental ones. The types of indicators discussed in the paper are designed to provide guidelines for measuring the degree of compliance. Using Pivot Pairwise Relatives Criteria Importance Assessment (PIPRECIA) method we have defined the evaluation of the mentioned indicators and their importance. The primary goal of the paper is to demonstrate the practical sides of the Multiple-Criteria Decision-Making (MCDM) methods in this sort of analysis while highlighting the most crucial sustainable tourism indicators.